2007
DOI: 10.1098/rspb.2007.0922
|View full text |Cite
|
Sign up to set email alerts
|

Influence of macrofaunal assemblages and environmental heterogeneity on microphytobenthic production in experimental systems

Abstract: Despite the complexity of natural systems, heterogeneity caused by the fragmentation of habitats has seldom been considered when investigating ecosystem processes. Empirical approaches that have included the influence of heterogeneity tend to be biased towards terrestrial habitats; yet marine systems offer opportunities by virtue of their relative ease of manipulation, rapid response times and the well-understood effects of macrofauna on sediment processes. Here, the influence of heterogeneity on microphytoben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 52 publications
3
47
1
Order By: Relevance
“…Resource availability and distribution, in particular, are fundamental in influencing community structure and species behaviour [4,51], and may also strongly modify ecosystem properties [18,19]. In contrast to previous studies that have demonstrated clear effects of biodiversity on ecosystem function under largely homogeneous conditions (e.g.…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…Resource availability and distribution, in particular, are fundamental in influencing community structure and species behaviour [4,51], and may also strongly modify ecosystem properties [18,19]. In contrast to previous studies that have demonstrated clear effects of biodiversity on ecosystem function under largely homogeneous conditions (e.g.…”
Section: Discussioncontrasting
confidence: 40%
“…To incorporate habitat heterogeneity, patches were either non-enriched (NE) or enriched (E) with dried, ground U. intestinalis [18,19]. We assembled two heterogeneity configurations (H A and H B ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, E. atakama spent 150 min relocating and 267 min feeding (a ratio of 1:1.8), suggesting that resource supply is indeed abundant and that the distance between patches is relatively short (20-40 min travel time, or approximately 10 body length distance). This pattern of movement suggests considerable sensitivity to food concentration (McClintic et al 2008) and implies that the dynamics and organisation of hadal communities are intimately linked to habitat structure and the distribution of resources in ways similar to those found in shallower benthic communities (Levinton and Kelaher 2004;Dyson et al 2007;Bulling et al 2008;Nogaro et al 2008;Godbold et al 2011). Thus, the cumulative response of hadal species to such small-scale variation is likely to influence species contributions to ecosystem properties at much larger scales (Godbold et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult for researchers to take full account of the complete environmental and biological context (Hewitt et al 2007); thus, the role these attributes play in mediating stressor impacts is not fully understood (Bishop and Kelaher 2013). Natural environments tend to be heterogeneous, whereas mesocosm or laboratory studies are generally controlled homogeneous environments (Dyson et al 2007). Natural heterogeneity has been observed to buffer against stressor effects (Godbold et al 2011) or negate patterns observed under laboratory conditions (Bulling et al 2008).…”
Section: Field Experimentationmentioning
confidence: 99%